“Relationship between Butyrylcholinesterase Activity and Cognitive Ability in Workers Exposed to Chlorpyrifos“ - Rosales-Rimache, Jaime (2023)
“Background. The use of Chlorpyrifos leads to a public, environmental, and occupational health problem associated with adverse effects in the exposed population, generating alterations mainly in the central nervous system, such as cognitive function. This study aimed to estimate the association between butyrylcholinesterase activity (BChE) and cognitive ability in workers exposed to chlorpyrifos. Methods. We designed a cross-sectional study, where we measured BChE in serum samples as an indicator of exposure to chlorpyrifos. The cognitive ability was assessed by the mean score of the Peruvian version of the Mini-Mental State Examination (MMSE). We also used a questionary to collect demographic and occupational information. Results. We evaluated 120 farmers with a predominance of males (92%) and a mean age of 32.1 ± 9.0 years. We found most of the workers in fumigation activities (84%). The mean BChE was 6144.7 ± 2355.0 U/L, and 46% presented inhibition enzyme (<5500 U/L). The median MMSE score was 28 (interquartile range: 26.5–31.5; 6% showed an alteration in cognitive ability (score < 24)). The MMSE test found a significant association between BChE inhibition and MMSE score (β: −0.071, 95%CI: −0.108 to −0.025). Conclusion. In this study, 45.8% of workers exposed to chlorpyriphos presented BChE inhibition. The BChE inhibition is significantly associated with the MMSE score in workers exposed to chlorpyrifos.“